2019
DOI: 10.1002/adsc.201900096
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Construction of 2,4‐Disubstituted Imidazoles via C–C Coupling and C−N Condensation Cascade Reactions

Abstract: A convenient Ni(II)‐catalyzed C−C and C−N cascade coupling reaction was developed to directly access various 2,4‐disubstituted imidazoles. The reaction scope covers a variety of aryl and aliphatic substitutions, which demonstrate moderate‐to‐excellent yields. The tolerance of halogen and N‐containing heterocyclic groups demonstrates the versatility of this method for further synthetic explorations.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Due to having donor‐acceptor property imadozole scaffold is of importance to synthesize bio‐active molecules, drugs and organic photovoltaic materials [22] . 2,4‐Disubstituted imidazoles were obtained via nickel‐catalyzed cascade coupling reaction involving C−C coupling followed by C−N coupling [23] . N ‐(cyanomethyl)‐acetamide 17 was employed in the coupling reaction with arylboronic acid 10 in presence of 10 mol% Ni(PPh 3 )Br 2 catalyst, 10 mol% of bispyridine ligand (L 5 ), 5 equiv.…”
Section: Nickel‐catalyzed Cascade Reaction For the Formation Of Heterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to having donor‐acceptor property imadozole scaffold is of importance to synthesize bio‐active molecules, drugs and organic photovoltaic materials [22] . 2,4‐Disubstituted imidazoles were obtained via nickel‐catalyzed cascade coupling reaction involving C−C coupling followed by C−N coupling [23] . N ‐(cyanomethyl)‐acetamide 17 was employed in the coupling reaction with arylboronic acid 10 in presence of 10 mol% Ni(PPh 3 )Br 2 catalyst, 10 mol% of bispyridine ligand (L 5 ), 5 equiv.…”
Section: Nickel‐catalyzed Cascade Reaction For the Formation Of Heterocyclesmentioning
confidence: 99%
“…[22] 2,4-Disubstituted imidazoles were obtained via nickel-catalyzed cascade coupling reaction involving CÀ C coupling followed by CÀ N coupling. [23] N-(cyanomethyl)-acetamide 17 was employed in the coupling reaction with arylboronic acid 10 in presence of 10 mol% Ni(PPh 3 )Br 2 catalyst, 10 mol% of bispyridine ligand (L 5 ), 5 equiv. sodium sulphate in anhydrous toluene at 120°C for 24 h producing the desired imidazole derivative 18 in low to good yields (13-89 %) (Scheme 5).…”
Section: Nickel-catalyzed Cascade Reaction For the Formation Of Heterocyclesmentioning
confidence: 99%
“…Fang et al reported a novel protocol for the cyclization of amido-nitriles 1 to form disubstituted imidazoles 2 (Scheme 1a). 19 The reaction conditions were mild enough for the inclusion of a variety of functional groups including, arylhalides as well as aromatic and saturated heterocycles (Scheme 1b). This reaction is reported to proceed via nickelcatalysed addition to nitrile 1, which followed by proto-demetallation, tautomerization and dehydrative cyclization afforded the desired 2,4-disubstituted NH-imidazoles 2 in poor to excellent yield depending on the coupling partners (Scheme 1c).…”
Section: One-bond Formedmentioning
confidence: 99%
“…[17] Besides, many imidazole and pyrimidine-based agents have been extensively studied as drug candidates and some of them are used clinically such as nilotinib, [18] metronidazole, [19] voriconazole, [20] eprosartan, and losartan. [21] Due to the wide range of applications of imidazole and pyrimidine cores, a variety of methods have been reported to the synthesis of them including various multi-component methods, [22][23][24][25][26] cyclization reaction, [22,[27][28][29] metal-catalyzed, [30][31][32][33] multistep approaches, [34,35] Diels-Alder reaction, [36] and various other methods. [37,38] However, the above-mentioned methods for synthesis of imidazole and pyrimidine derivatives suffer from one or more disadvantages, for example difficult reaction conditions, low yields, complex work-up and purification, multiple synthetic steps, and usage of expensive catalysts and reagents.…”
Section: Introductionmentioning
confidence: 99%